Hadith #821 - Sahih al-Bukhari - Abu al-Zanad أبو الزناد (Sahih al-Bukhari)
(the freed slave of Ibn `Abbas) Ibn `Abbas told me, “In the lifetime of the Prophet (ﷺ) it was the custom to celebrate Allah’s praises aloud after the compulsory congregational prayers.” Ibn `Abbas further said, “When I heard the Dhikr, I would learn that the compulsory congregational prayer had ended.”
Grade: Sahih

Hadith #1444 - Sahih al-Bukhari - Abu al-Zanad أبو الزناد (Sahih al-Bukhari)
(the slave of Ibn `Abbas) Allah’s Messenger (ﷺ) said to Mu`adh when he sent him to Yemen, “You will go to the people of the Scripture. So, when you reach there, invite them to testify that none has the right to be worshipped but Allah, and that Muhammad is His Apostle. And if they obey you in that, tell them that Allah has enjoined on them five prayers in each day and night. And if they obey you in that tell them that Allah has made it obligatory on them to pay the Zakat which will be take
Grade: Sahih